A diagnosis of the role of integrative and instrumental motivations in the process of learning english as a foreign language : the case of third-year students from modern languages major, semester II-2013, at the Foreign Languages Department, UES. - Alvarez, Marta Azucena; Hernández López, Cristina Iveth; Solis Quijada, Wendi Martina; Franco Ramos, Rhina; Ayala, Edgar Nicolas (SanSalvador El Salvador : Universidad de El Salvador, 2014)
Nowadays the English language has become a fundamental tool in international business communication and the most used language around the world. Due to that fact, learning English has become a need for people in order to get better job opportunities, to connect with other cultures, or to have access to up-to-date information. However, learning this language is not as easy as people may think because many factors are involved in this process. Among those important elements we find Motivation, which, to our judgment, is one of the most important ones. Motivation is at the heart of learning a foreign language since it is the force which drives people to achieve their goals. Because of that, some experts in the linguistic field such as Gardner and Lambert, Ellis and Brown agreed that language learning motivation can be divided into two types: Integrative and Instrumental Motivations, a sub-category of Extrinsic motivation. The first one shows the desire of students to integrate themselves to the target language community and the second one involves learning the language with instrumental reasons. Being aware of it, this study was conducted in order to find out the role of both types of motivation in the process of learning English and which of them predominates the most among third-year students from Modern Languages Major at the Foreign Languages Department of the University of El Salvador during semester II-2013.
Anexos.
Bibliográfia : hojas 56-57
Keywords: Inglés -- Enseñanza; Adquisición de segundo lenguaje